2021
DOI: 10.1002/da.23190
|View full text |Cite
|
Sign up to set email alerts
|

Examining reciprocal associations between parent depressive symptoms and child internalizing symptoms on subsequent psychiatric disorders: An adoption study

Abstract: Introduction:The dynamic interplay between parent depressive symptoms and child internalizing behavior over time is not well understood. Methods:We used data from a prospective parent-offspring adoption design (N = 561) to examine associations between adoptive parent depressive symptoms and child internalizing behavior when children were ages 18 months, 27 months, 4.5 years, and 6 years, and subsequent child psychiatric disorder symptoms when children were between the ages of 6-8 years. Models also accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…The results of Cioffi, Leve, et al (2021) dovetail with the results of an additional EGDS analysis that explored predictors of changes in children's internalizing and externalizing symptoms from 18 to 54 months within a latent growth curve model (Kerr et al, 2013). This study found evidence of modest direct associations between adoptive mothers' depressive symptoms and children's levels of internalizing and externalizing symptoms at 18 months, after heritable influences (as indexed by birth mother depressive symptoms) and prenatal risks were statistically controlled.…”
Section: Estimating Unconfounded Parenting Effects Via the Adoption D...mentioning
confidence: 68%
See 3 more Smart Citations
“…The results of Cioffi, Leve, et al (2021) dovetail with the results of an additional EGDS analysis that explored predictors of changes in children's internalizing and externalizing symptoms from 18 to 54 months within a latent growth curve model (Kerr et al, 2013). This study found evidence of modest direct associations between adoptive mothers' depressive symptoms and children's levels of internalizing and externalizing symptoms at 18 months, after heritable influences (as indexed by birth mother depressive symptoms) and prenatal risks were statistically controlled.…”
Section: Estimating Unconfounded Parenting Effects Via the Adoption D...mentioning
confidence: 68%
“…For example, Perez Grabow (2017) noted significant associations between adoptive mothers' depressive symptoms and children's internalizing symptoms at age 7 years. A more comprehensive analysis led by Cioffi used a random intercept cross‐lagged panel model to examine associations between adoptive parents' depressive symptoms and children's internalizing symptoms from 18 months to 6 years (Cioffi, Leve, et al, 2021). The random intercept model can be used to estimate the average association between adoptive mother's depressive symptoms and children's internalizing symptoms across families and over time (i.e., between‐family effects).…”
Section: Estimating Unconfounded Parenting Effects Via the Adoption D...mentioning
confidence: 99%
See 2 more Smart Citations
“…One similar study has used the TSO model to examine the effects of maternal anxiety and depressive symptoms (measured from child ages 3 months to 12.5 years) on adolescent internalizing problems, and reported that maternal trait-like symptoms, but not time-specific fluctuations in symptoms, were associated with adolescent internalizing problems (Missler et al, 2021). However, time-specific influences of parent anxiety and depressive symptoms on child and adolescent internalizing problems have been reported elsewhere (Cioffi et al, 2021;Xerxa et al, 2021). Moreover, Missler et al (2021) examined biological parents rearing their biological children, thus the association between parent and child anxiety and depressive symptoms may be confounded by shared genetics factors, especially for the association between maternal trait-like symptoms and adolescent symptoms, as stability of anxiety and depressive symptoms are mostly explained by genetic influences (Nivard et al, 2015).…”
mentioning
confidence: 99%